Outlining a Population “at Risk” of Parkinson’s Disease: Evidence from a Case-Control Study - Tommaso Schirinzi; Giuseppina Martella; Alessio D’Elia; Giulia Di Lazzaro; Paola Imbriani; Graziella Madeo; Leonardo Monaco; Marta Maltese; Antonio Pisani (Parkinson's Disease, 2016)
The multifactorial pathogenesis of Parkinson’s Disease (PD) requires a careful identification of populations “at risk” of developing the disease. In this case-control study we analyzed a large Italian population, in an attempt to outline general criteria to define a population “at risk” of PD. We enrolled 300 PD patients and 300 controls, gender and age matched, from the same urban geographical area. All subjects were interviewed on demographics, family history of PD, occupational and environmental toxicants exposure, smoking status, and alcohol consumption. A sample of 65 patients and 65 controls also underwent serum dosing of iron, copper, mercury, and manganese by means of Inductively Coupled-Plasma-Mass-Spectrometry (ICP-MS). Positive family history, toxicants exposure, non-current-smoker, and alcohol nonconsumer status occurred as significant risk factors in our population. The number of concurring risk factors overlapping in the same subject impressively increased the overall risk. No significant differences were measured in the metal serum levels. Our findings indicate that combination of three to four concurrent PD-risk factors defines a condition “at risk” of PD. A simple stratification, based on these questionnaires, might be of help in identifying subjects suitable for neuroprotective strategies.